Pleasantville [videorecording (DVD)] - Ross, Gary, 1956-; Maguire, Tobey, 1975-; Witherspoon, Reese, 1976-; Daniels, Jeff, 1955-; Allen, Joan, 1956- (New Line platinum series, 1999)
A brother and sister are magically transported through their television set and into the black-and-white world of a 1950s sitcom called Pleasantville. Soon they affect this environment with their worldly sensibilities, and people and things slowly begin to acquire color.